Analysis of Education Quality Mapping Based on Geographical Information System (GIS) - Zuqoni, Zuqoni; Rahman, Fathur; Susmiyati, Sri; Saugi, Wildan (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Improving the quality of education is an integral part of the government's program. Enhancing the quality of education requires mapping based on educational levels and regions to provide an up-to-date depiction of the implementation and distribution of education. The purpose of this research is to map the quality of education in East Kalimantan based on the Geographical Information System (GIS). One of the government's accelerated development programs is to ensure equal distribution in improving the quality of education across all regions of the Republic of Indonesia. One step in implementing this program is mapping the quality of education through schools. Mapping the quality of education through schools is expected to portray the actual conditions in the field. The mapping is intended to generate evaluations, policies, recommendations, and planning programs for future education quality improvement. This research discusses mapping education quality using a geographical mapping method through observation and interviews. The collected data is subsequently grouped according to the boundaries of each region, designing maps based on the geographical conditions of the areas to be mapped. OpenJUMP software for GIS is utilized to integrate observation data and polygon maps of East Kalimantan, describing the analysis results for each mapped area. The implementation of the research findings and drawing conclusions will use Ms. Excel 2010 and Open Jump for GIS. The conclusion drawn from the GIS-based education quality mapping is that the clustering method can effectively visualize the distribution of education quality for each area, facilitating visual analysis. Mapping Education Quality in East Kalimantan based on Geographic Information System (GIS) is capable and effective in spatially identifying the distribution of education quality. Based on the grouping according to 8 parameters of the National Education Standards, it is concluded that several parameters, particularly Infrastructure Standards and Process Standards, have the highest number of categories not meeting the National Education Standards in each mapped area. This indicates that each parameter of the National Education Standards is still unevenly implemented.